Magnetic resin composition, magnetic film and application thereof

By compounding specific types and amounts of magnetic fillers, the contradiction between magnetic properties and processability of magnetic films under high filling conditions was resolved, achieving high permeability and low magnetic loss at high frequencies, and improving the adhesion to the copper layer to ensure circuit stability.

CN121064597APending Publication Date: 2025-12-05GUANGDONG SHENGYI SCI TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510158434.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing magnetic thin films, under high fill conditions, struggle to balance magnetic properties with processability, especially at high frequencies where high permeability and low magnetic loss cannot be achieved simultaneously. Furthermore, insufficient bonding with copper wires leads to circuit failure.

Method used

A magnetic resin composition was prepared by compounding specific types and amounts of magnetic fillers (carbonyl iron powder, FeSiCr alloy and iron-based nanocrystalline alloy, FeSiCr alloy, iron-based nanocrystalline). By introducing specific methods, epoxy resin, curing agent and toughening agent were combined to improve the processability of the magnetic film and its adhesion to the copper layer.

Benefits of technology

High permeability and low magnetic loss were achieved at high frequencies, while the bonding force between the magnetic thin film and the copper layer was improved, resolving the contradiction between magnetic properties and processability and avoiding circuit failure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121064597A_ABST
    Figure CN121064597A_ABST
Patent Text Reader

Abstract

The invention provides a magnetic resin composition, a magnetic film and application thereof. The magnetic resin composition comprises (A) a magnetic filler, (B) epoxy resin, (C) a curing agent and (D) a flexibilizer, the magnetic filler (A) comprises carbonyl iron powder (A1), FeSiCr alloy (A2) and iron-based nanocrystals (A3); based on the total mass of the magnetic resin composition as 100%, the content of the (A) magnetic filler is 85% or more; based on 100% of the total mass of the magnetic filler (A), the content of the carbonyl iron powder (A1) is 55%-65%, the content of the FeSiCr alloy (A2) is 15%-25%, and the content of the iron-based nanocrystalline (A3) is 15%-25%. According to the magnetic resin composition and the preparation method thereof, specific types of magnetic fillers are introduced and compounded according to a specific content, so that the magnetic resin composition has relatively high magnetic conductivity and relatively low magnetic loss after being cured, and meanwhile, the binding force with a copper layer is relatively high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor device technology, specifically relating to a magnetic resin composition, a magnetic thin film, and their applications. Background Technology

[0002] Magnetic thin films primarily function as magnetic cores in inductor applications, forming inductor components together with conductive coils. Compared to traditional magnetic cores, magnetic thin films have the following characteristics:

[0003] 1. Higher operating frequency: Due to the extremely thin magnetic film, eddy current loss at high frequencies can be effectively suppressed, making it suitable for higher operating frequencies, up to GHz or even higher.

[0004] 2. Smaller size and higher integration: Magnetic thin film technology can realize micron or even nanometer-scale structures, making inductor components very small and easy to integrate with other microelectronic devices on the same chip or substrate.

[0005] 3. Better performance consistency: The magnetic thin film fabrication process can precisely control the thickness, composition and structure of the film, thereby obtaining inductor components with better performance consistency.

[0006] Embedded inductors are a technology that integrates inductor components within a circuit board or package. Magnetic thin films are ideally suited for manufacturing embedded inductors. The process of integrating thin-film inductors into a substrate or package includes steps such as thin-film deposition, photolithography, etching, and electroplating, and must be compatible with the materials and processes of the substrate or package.

[0007] Embedded inductors are widely used in radio frequency circuits, power management circuits, high-speed digital circuits, and other fields. They are especially important in applications with high requirements for miniaturization and integration, such as mobile communications, wireless networks, and wearable devices.

[0008] The above demonstrates the advantages of using magnetic thin films for embedded, integrated inductors. However, a trade-off exists in the fabrication process between the finished magnetic properties and the processability. Finished inductors require higher permeability to achieve their core performance requirements, such as inductance. This necessitates the addition of more magnetic filler, often exceeding 85 wt.%. Under such high filler content, the magnetic thin film is not only brittle and difficult to handle, but its most critical drawback is its extremely low adhesion to copper wires. This makes the copper wires highly susceptible to detachment during subsequent processing, leading to circuit failure. Furthermore, permeability and magnetic loss are inversely related; existing magnetic thin films cannot achieve a balance between permeability and magnetic loss at high frequencies (100MHz).

[0009] Therefore, it is desirable in this field to develop a magnetic resin composition for use in magnetic thin films and magnetic circuit devices that can resolve the contradiction between the magnetic properties and processability of the devices, while still maintaining high permeability and low magnetic loss at high frequencies. Summary of the Invention

[0010] To address the shortcomings of existing technologies, the present invention aims to provide a magnetic resin composition, a magnetic thin film, and their applications. This invention significantly optimizes the processability of the magnetic thin film by introducing specific types and amounts of magnetic fillers in a combined formulation. The resulting circuit exhibits very high adhesion to the substrate, overcoming the challenge of simultaneously achieving processability and magnetic properties at high filler content. Furthermore, the magnetic thin film provided by this invention maintains both high permeability and low magnetic loss at high frequencies (100MHz).

[0011] To achieve this objective, the present invention employs the following technical solution:

[0012] In a first aspect, the present invention provides a magnetic resin composition comprising the following components:

[0013] (A) Magnetic filler, (B) Epoxy resin, (C) Curing agent, (D) Toughening agent;

[0014] The magnetic filler (A) comprises the following components: (A1) carbonyl iron powder, (A2) FeSiCr alloy and (A3) iron-based nanocrystals.

[0015] Based on the total mass of the magnetic resin composition (excluding solvent) as 100%, the content of the magnetic filler (A) is 85% or more, for example, it can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or 98%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0016] Based on the total mass of the magnetic filler (A) being 100%, the content of the carbonyl iron powder (A1) is 55%-65% (for example, it can be 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, or 65%, and specific values ​​between the above points; for space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range), and the content of the FeSiCr alloy (A2) is 15%-25% (for example, it can be 15%, 16%, 17%, 18%, 19%, 2%). The content of (A3) iron-based nanocrystals is 15%-25% (for example, it can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%, and the specific values ​​between the above points are not exhaustively listed in this invention due to space limitations and for the sake of brevity).

[0017] The magnetic resin composition provided by the present invention introduces specific types of magnetic fillers and is compounded in specific amounts, so that after the magnetic resin composition is cured, it has high magnetic permeability and low magnetic loss at high frequency (100MHz), and at the same time has high adhesion to copper layer (sputtered copper + electroplating).

[0018] Preferably, the content of the magnetic filler (A) is 85%-95% based on 100% of the total mass of the magnetic resin composition.

[0019] Preferably, the particle size characteristics of the (A1) carbonyl iron powder are: D50 = 1.2-2 μm, for example, it can be 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2 μm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0020] Preferably, the particle size characteristics of the (A2)FeSiCr alloy are: D50 = 4-6 μm, for example, it can be 4 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm, 5 μm, 5.2 μm, 5.4 μm, 5.6 μm, 5.8 μm or 6 μm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0021] Preferably, the particle size characteristics of the (A3) iron-based nanocrystals are: D50 = 7-8 μm, for example, 7 μm, 7.2 μm, 7.4 μm, 7.6 μm, 7.8 μm or 8 μm, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0022] The particle size of the filler in this paper was obtained by testing with a Malvern 3000 laser particle size analyzer.

[0023] Preferably, in this invention, the main component of the iron-based nanocrystals is iron (Fe), with small amounts of other elements added to improve their magnetic properties, corrosion resistance, or other properties. These elements typically include one or more of the following:

[0024] Copper (Cu): Promotes the formation of nanocrystals.

[0025] Niobium (Nb): Inhibits grain growth and maintains nanocrystalline structure.

[0026] Silicon (Si): Improves magnetic permeability and reduces losses.

[0027] Boron (B): Enhances glass-forming ability and facilitates rapid solidification.

[0028] Preferably, the iron-based nanocrystals include FeSiBNbCu nanocrystals.

[0029] Preferably, the epoxy resin (B) comprises any one or a combination of at least two of crystalline epoxy resin, bisphenol epoxy resin, and glycidyl ester epoxy resin.

[0030] Preferably, the curing agent (C) includes any one or a combination of at least two of amine curing agents and phenolic curing agents.

[0031] Preferably, the toughening agent (D) comprises any one or a combination of at least two of rubber, acrylic resin, and phenolic resin.

[0032] Preferably, based on the total mass of components (B), (C), and (D) being 100%, the amount of epoxy resin (B) is 40%-80% (e.g., 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, or 80%, and specific values ​​between these ranges; for space limitations and for the sake of brevity, the present invention will not exhaustively list all the specific values ​​included in the ranges), and the amount of curing agent (C) is 10%-25% (e.g., 1 ...%). The amounts of the toughening agent (D) are 10%-35% (e.g., 10%, 15%, 18%, 20%, 22%, 23%, or 25%, and specific values ​​between the above values; for the sake of space and brevity, this invention will not exhaustively list all the specific values ​​included in the range).

[0033] Preferably, the magnetic resin composition further includes (E) a curing accelerator.

[0034] Preferably, the amount of curing accelerator (E) is 0.01%-0.05% based on 100% of the total organic matter (i.e., the total of components other than (A) magnetic filler and solvent) in the magnetic resin composition, for example, 0.01%, 0.03% or 0.05%, and specific values ​​between the above values ​​are not exhaustively listed in this invention for space limitations and for the sake of brevity.

[0035] Preferably, a solvent may also be added to the magnetic resin composition. The amount of solvent added is selected by those skilled in the art based on experience and process requirements, so that the magnetic resin composition reaches a suitable viscosity for use, facilitating impregnation, coating, etc. Subsequently, during drying, semi-curing, or complete curing stages, the solvent in the magnetic resin composition will partially or completely evaporate.

[0036] The solvent used in this invention is not particularly limited, and generally can be ketones such as acetone, butanone, and cyclohexanone; aromatic hydrocarbons such as toluene and xylene; esters such as ethyl acetate and butyl acetate; alcohols such as methanol, ethanol, or butanol; alcohols such as ethyl cellosolve, butyl cellosolve, ethylene glycol monomethyl ether, carbitol, or butyl carbitol; and nitrogen-containing solvents such as N,N-dimethylformamide (DMF), N,N-dimethylacetamide, or N-methyl-2-pyrrolidone. The solvent can be used alone or in mixtures of two or more. Preferably, ketones such as acetone, butanone, and cyclohexanone, and nitrogen-containing solvents such as N,N-dimethylformamide (DMF) and N,N-dimethylacetamide are used.

[0037] The magnetic resin composition provided by the present invention is prepared by the following method, the preparation method comprising: mixing and dispersing the components in the magnetic resin composition evenly to obtain the magnetic resin composition.

[0038] In a second aspect, the present invention provides a magnetic film, which is obtained by coating a release material with the magnetic resin composition described in the first aspect and then drying it.

[0039] Preferably, the thickness of the magnetic thin film is 50-200 μm, for example, it can be 50 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm or 200 μm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0040] Preferably, the release material includes a PET (polyethylene terephthalate) film.

[0041] Thirdly, the present invention provides a magnetic circuit device, the magnetic circuit device comprising at least one magnetic thin film as described in the second aspect.

[0042] Preferably, the magnetic circuit device includes a magnetic thin film and a copper coil embedded in the magnetic thin film.

[0043] Fourthly, the present invention provides a method for fabricating a magnetic circuit device as described in the third aspect, the method comprising the following steps:

[0044] (1) The magnetic film and the first copper coil are vacuum hot-pressed together and completely cured to obtain a magnetic layer embedded with the first copper coil.

[0045] (2) Grind the plate, expose the copper wire, clean and dry it, continue to make the second copper coil on the copper wire to form the interconnection between the first copper coil and the second copper coil, and then vacuum heat press and solidify the second magnetic film with the second copper coil.

[0046] (3) Optionally, repeat step (2) to obtain a magnetic circuit device with a multilayer structure, each layer containing a magnetic thin film and a copper coil, and the layers being interconnected.

[0047] It should be noted that the exposed copper wire in the grinding plate does not need to expose the entire copper coil; only a portion needs to be exposed. The exposed copper wire serves as a connection point to the copper coil subsequently manufactured. Furthermore, the shape of the subsequently manufactured copper coil can be varied freely and does not need to be the same as the shape of the copper coil manufactured in the previous step.

[0048] Because the magnetic filler content in the magnetic film needs to reach a high level (above 85 wt.%), the adhesion between the magnetic film and the copper wire fabricated above will be very low, which may cause wire breakage and short circuits in subsequent processing, leading to circuit failure. This invention improves the bonding performance between the resin and the magnetic filler by using a combination of three types and specific amounts of magnetic fillers, thereby enhancing the adhesion between the magnetic film and the copper wire.

[0049] Preferably, the multilayer consists of 2-3 layers.

[0050] Fifthly, the present invention provides an application of the magnetic circuit device as described in the third aspect in embedded inductors or surface-mount inductors.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] The magnetic resin composition provided by the present invention introduces specific types of magnetic fillers and blends them in specific amounts, so that after the magnetic resin composition is cured, it has high magnetic permeability and low magnetic loss at high frequencies, and at the same time has high adhesion to copper layers (sputtered copper + electroplating). Attached Figure Description

[0053] Figure 1 The image shows the SEM image of the magnetic thin film plate provided in Example 1 after grinding, cleaning, and drying.

[0054] Figure 2 The image shows the SEM image of the magnetic thin film plate provided in Example 2 after grinding, cleaning, and drying.

[0055] Figure 3 SEM images of the magnetic thin film plate after grinding, cleaning, and drying, provided for Comparative Example 2.

[0056] Figure 4 SEM images of the magnetic thin film plate provided in Comparative Example 3 after grinding, cleaning, and drying.

[0057] Figure 5 SEM images of the magnetic thin film plate provided in Comparative Example 4 after grinding, cleaning, and drying.

[0058] Figure 6 This is a schematic diagram of the appearance of the test sample prepared for testing the bonding force between the magnetic thin film and the copper wire in this invention. Detailed Implementation

[0059] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.

[0060] In the following specific embodiments of the present invention, the materials involved are as follows:

[0061] (A1) Carbonyl iron powder

[0062] Carbonyl iron powder, grade YF-T6A, D50 is 1.6μm, Jiangxi Yuean New Material Co., Ltd.;

[0063] Carbonyl iron powder, grade MFe-S10, with a D50 of 6μm, manufactured by Zhejiang Quanding Magnetoelectric Materials Co., Ltd.

[0064] (A2)FeSiCr alloy

[0065] FeSiCr alloy, grade EA-SMP-10PF-5KG, D50 is 4.26μm, manufactured by EPSON ATMIX CORPORATION;

[0066] FeSiCr alloy, grade EA-SMP-10PF-20F, D50 is 10μm, manufactured by EPSON ATMIX CORPORATION;

[0067] (A3) Iron-based nanocrystals

[0068] Iron-based nanocrystals, grade ATFINE-NC1 PF-13FA, D50 is 8μm, manufactured by EPSON ATMIX CORPORATION;

[0069] Iron-based nanocrystals, grade QNM-NC1, with a D50 of 10μm, manufactured by Zhejiang Quanding Magnetoelectric Materials Co., Ltd.

[0070] (B) Epoxy resin

[0071] Crystalline biphenyl epoxy resin: Grade YX-4000, manufactured by Mitsubishi Chemical Corporation;

[0072] Crystalline biphenyl epoxy resin: Grade NC3000H, manufactured by Nippon Kayaku Co., Ltd.

[0073] Bisphenol A type epoxy resin: grade NPES-901, manufactured by Nan Ya Electronic Materials Co., Ltd.

[0074] Bisphenol A type epoxy resin: Grade 828US, manufactured by Mitsubishi Chemical Corporation;

[0075] Glycidyl ester type epoxy resin: Grade EX-321L, manufactured by Nagase ChemteX Co., Ltd.

[0076] (C) Curing agent

[0077] Amine curing agent: DDS (4,4'-diaminodiphenyl sulfone);

[0078] Phenolic curing agent: MEH-7851, manufactured by Meiwa Kasei Corporation;

[0079] (D) Toughening agent

[0080] Core-shell rubber: Model M-521, Kanekachi Chemical Co., Ltd., Japan;

[0081] Core-shell rubber: Model Clearstrength XT100, manufactured by ARKEMA;

[0082] Acrylic resin: Model LP-3104, manufactured by Mitsubishi Chemical Corporation;

[0083] Acrylic resin: Model AR42W, manufactured by Guangzhou Weiyang;

[0084] Phenoxy resin: Model BPRS-EK30, manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.

[0085] (E) Curing accelerator

[0086] 2-PZ(2-phenylimidazole).

[0087] Example 1

[0088] This embodiment provides a magnetic resin composition, the specific components and amounts (parts by weight) of which are shown in Table 1.

[0089] This embodiment also provides a magnetic thin film, the preparation method of which includes the following steps:

[0090] According to the formulation in Table 1, each component was mixed with a solvent (a mixture of MEK (butanone) and PM (propylene glycol monomethyl ether) in a mass ratio of 1:1) to obtain a glue solution with a solid content of 90%. The glue solution was coated onto a release material (PET film) and dried to obtain the magnetic film with a thickness of 150 μm.

[0091] This embodiment also provides a magnetic circuit device, the fabrication method of which includes the following steps:

[0092] The magnetic film is vacuum heat-pressed with the first copper coil and completely cured to obtain a magnetic layer containing the first copper coil. After grinding the plate and exposing part of the copper wire, it is cleaned and dried. A second copper coil is then fabricated on the copper wire to form an interconnection between the first and second copper coils. Another magnetic film is then vacuum heat-pressed with the second copper coil and cured to obtain a magnetic circuit device with a two-layer structure, each layer containing a magnetic film and a copper coil, and the two layers are interconnected.

[0093] Examples 2-8, Comparative Examples 1-6

[0094] The only difference from Example 1 is that the specific components and / or amounts of the magnetic resin composition are different, as shown in Tables 1 and 2.

[0095] Table 1

[0096]

[0097]

[0098] Table 2

[0099]

[0100] Performance testing

[0101] (1) The magnetic thin films provided in Examples 1-2 and Comparative Examples 2-4 of the present invention were ground, cleaned, and dried. Then, the magnetic thin films were characterized by scanning electron microscopy (SEM). The characterization results are as follows: Figures 1-5 As shown, compared to adding only a single type of magnetic filler (Comparative Examples 2-4), the magnetic film with added (A1) to (A3) magnetic fillers has a better morphology after grinding, and the filler and resin are well bonded. In the magnetic film provided by Comparative Example 2, the resin cannot effectively coat the magnetic filler, and most of the filler is exposed on the surface, which cannot achieve bonding with the copper layer. In the magnetic film provided by Comparative Example 3, all the magnetic filler is ground off, resulting in excessively large pits, which also cannot achieve good bonding with the copper layer. The magnetic film provided by Comparative Example 4 is in a state between Comparative Example 2 and Comparative Example 3, and still cannot achieve good bonding with the copper layer.

[0102] (2) The magnetic films provided in the above embodiments and comparative examples of the present invention are ground, cleaned, and dried, and then strip-shaped copper wires are pressed onto the magnetic film (see the schematic diagram of the appearance of the test sample as shown in the figure). Figure 6 As shown), the bonding force between the magnetic thin film and the copper wire was tested. The test method was based on IPC-TM-650 2.4.8 (version 12 / 94C).

[0103] (3) The magnetic permeability and magnetic loss of the magnetic circuit devices provided in the above embodiments and comparative examples of the present invention are tested. The test method is as follows: The magnetic board is processed into a ring sample (inner diameter 5.5mm, outer diameter 19.5mm, thickness 2mm) using a CNC milling machine. The magnetic permeability and magnetic loss of the ring sample at 100MHz are tested using an impedance analyzer (Keysight E4991B).

[0104] The test results are shown in Table 3.

[0105] Table 3

[0106]

[0107]

[0108] As can be seen from Table 3, the magnetic thin films and copper wires provided in Examples 1-5 of the present invention all have high bonding strength (0.43-0.61 N / mm), and the magnetic circuit devices prepared all have high permeability (8.12-8.60) and low magnetic loss (0.025-0.030).

[0109] Compared with Example 1, the bonding strength between the magnetic films and copper wires provided in Comparative Examples 1-4 and Comparative Example 6 was significantly reduced, and both high permeability and low magnetic loss could not be achieved simultaneously. Although Comparative Example 5 could achieve both permeability and magnetic loss, the bonding strength was only 0.18 N / mm, which still could not meet the requirements for process use.

[0110] The applicant declares that the magnetic resin composition, magnetic film, and their applications of the present invention are illustrated through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A magnetic resin composition, characterized by comprising: The magnetic resin composition comprises the following components: (A) a magnetic filler, (B) an epoxy resin, (C) a curing agent, (D) a toughening agent; The (A) magnetic filler comprises the following components: (A1) a carbonyl iron powder, (A2) a FeSiCr alloy, and (A3) an iron-based nanocrystal; The content of the (A) magnetic filler is 85% or more, based on the total mass of the magnetic resin composition; The content of the (A1) carbonyl iron powder is 55%-65%, the content of the (A2) FeSiCr alloy is 15%-25%, and the content of the (A3) iron-based nanocrystal is 15%-25%, based on the total mass of the (A) magnetic filler.

2. The magnetic resin composition according to claim 1, characterized by The content of the (A) magnetic filler is 85%-95%, based on the total mass of the magnetic resin composition.

3. The magnetic resin composition according to claim 1 or 2, characterized by The particle size characteristics of the (A1) carbonyl iron powder are: D50 = 1.2-2 μm; Preferably, the particle size characteristics of the (A2) FeSiCr alloy are: D50 = 4-6 μm; Preferably, the particle size characteristics of the (A3) iron-based nanocrystal are: D50 = 7-8 μm.

4. The magnetic resin composition according to any one of claims 1 to 3, characterized by, The (B) epoxy resin comprises any one or a combination of at least two of a crystalline epoxy resin, a bisphenol-type epoxy resin, and a glycidyl ester-type epoxy resin; Preferably, the (C) curing agent comprises any one or a combination of at least two of an amine-type curing agent and a phenolic-type curing agent; Preferably, the (D) toughening agent comprises any one or a combination of at least two of a rubber, an acrylic resin, and a phenolic resin.

5. The magnetic resin composition according to any one of claims 1 to 4, characterized by, The amount of the (B) epoxy resin is 40%-80%, the amount of the (C) curing agent is 10%-25%, and the amount of the (D) toughening agent is 10%-35%, based on the total mass of the components (B), (C), and (D).

6. The magnetic resin composition according to any one of claims 1 to 5, characterized by, The magnetic resin composition further comprises an (E) curing accelerator; Preferably, the amount of the (E) curing accelerator is 0.01%-0.05%, based on the total mass of the organic substances in the magnetic resin composition.

7. A magnetic thin film, characterized by, The magnetic thin film is prepared by drying the magnetic resin composition of any one of claims 1-6 coated on a release material; Preferably, the thickness of the magnetic thin film is 50-200 μm; Preferably, the release material comprises a PET film.

8. A magnetic circuit device, characterized by comprising: The magnetic circuit device comprises at least one magnetic thin film as claimed in claim 7; Preferably, the magnetic circuit device comprises a magnetic thin film and a copper coil embedded in the magnetic thin film.

9. A method of manufacturing a magnetic circuit device as claimed in claim 8, characterized in that The preparation method comprises the following steps: (1) vacuum hot-pressing the magnetic thin film and a first copper coil, and after complete curing, obtaining a magnetic layer embedded with the first copper coil; (2) grinding the plate, washing and drying after exposing the copper coil, continuing to make a second copper coil on the copper coil, forming an interconnection of the first copper coil and the second copper coil, and then vacuum hot-pressing a second magnetic thin film and the second copper coil and curing; (3) optionally, repeating step (2) to obtain a magnetic circuit device comprising a multi-layer structure, each layer comprising a magnetic thin film and a copper coil, and the layers being interconnected. Preferably, the multiple layers are 2-3 layers.

10. Use of a magnetic circuit device as claimed in claim 8 in a buried inductor or a surface mounted inductor.

Citation Information

Cited By

  • Design method of winding magnetic ring with electromagnetic interference suppression effect regulation and control characteristic

    CN122153998A